FOXG1 syndrome: genotype–phenotype association in 83 patients with FOXG1 variants - Mitter, Diana; Pringsheim, Milka; Kaulisch, Marc; Plümacher, Kim Sarah; Schröder, Simone; Warthemann, Rita; Abou Jamra, Rami; Baethmann, Martina; Bast, Thomas; Büttel, Hans-Martin; Cohen, Julie S.; Conover, Elizabeth; et al. (Genetics in medicine, 2018)
Purpose: The study aimed at widening the clinical and genetic spectrum and assessing genotype-phenotype associations in FOXG1 syndrome due to FOXG1 variants. Methods: We compiled 30 new and 53 reported patients with a heterozygous pathogenic or likely pathogenic variant in FOXG1. We grouped patients according to type and location of the variant. Statistical analysis of molecular and clinical data was performed using Fisher's exact test and a nonparametric multivariate test. Results: Among the 30 new patients, we identified 19 novel FOXG1 variants. Among the total group of 83 patients, there were 54 variants: 20 frameshift (37%), 17 missense (31%), 15 nonsense (28%), and 2 in-frame variants (4%). Frameshift and nonsense variants are distributed over all FOXG1 protein domains; missense variants cluster within the conserved forkhead domain. We found a higher phenotypic variability than previously described. Genotype-phenotype association revealed significant differences in psychomotor development and neurological features between FOXG1 genotype groups. More severe phenotypes were associated with truncating FOXG1 variants in the N-terminal domain and the forkhead domain (except conserved site 1) and milder phenotypes with missense variants in the forkhead conserved site 1. Conclusions: These data may serve for improved interpretation of new FOXG1 sequence variants and well-founded genetic counseling.